Study and Analysis of a New Device for the Rehabilitation of the Tibiotarsal Joint - Cruz, Ana (2020)
Introduction: Currently, there are several types of devices and techniques for the rehabilitation of the tibiotarsal joint. However, complete and effective rehabilitation still falls short of expectations, since the existing devices are not adaptable to the level of torque and the number of repetitions and sessions to be performed, as these depend on each patient and on the stage at which he is finds. Objetives: To improve a mechatronic device for the rehabilitation of the tibiotarsal joint, the Therapheet. Methods: This study presents a review of the tibiotarsal joint rehabilitation protocols, as well as the classification of devices used for this purpose. Thus, the purpose is to improve the Therapheet, developed at the Department of Mechanical Engineering of the University of Minho, obtaining a viable, functional and safe rehabilitation device, standing out from the rest on the market, since it allows the execution of the six rehabilitation exercises. Results: It was obtained a prototype of equipment for rehabilitation of the tibiotarsal joint was obtained, proposing changes for improvement according to the specificities and requirements for such a device, having been subjected to a series of preliminary tests to verify its functionality, performance and suitability. The equipment proved to be functional, in terms of executing the ankle rehabilitation movements, however, it still manifests some flaws in terms of the user's stability, sudden movements, and above all dysfunctions arising from excess mass that make up its structure and limitations pneumatic technology adopted. Conclusions: The control of the amplitude of the characteristic angles of the movements of the foot is still done manually, so it would be significant to implement an automated system that would allow the control of the range of amplitude, according to the patient's rehabilitation phase. One option would be the implementation of a new technology, such as the insertion of servomotors.